Ladybirds - Althea; McGirr, Barbara ([Essex, England] : Longman, 1985)
Bright illustrations and simple text describe the life cycle and beneficial habits and behavior of the ladybug.
2.0
K-3
Keywords: Ladybugs -- Juvenile literature; Ladybugs; Ladybugs